Microparticles in contact with cells: from carriers to multifunctional tissue modulators - Neto, Mafalda D. (2022)
For several decades microparticles have been exclusively and extensively explored as spherical drug delivery vehicles and large-scale cell expansion carriers. More recently, microparticulate structures gained interest in broader bioengineering fields, integrating myriad strategies that include bottom-up tissue engineering, 3D bioprinting, and the development of tissue/disease models. The concept of bulk spherical micrometric particles as adequate supports for cell cultivation has been challenged, and systems with finely tuned geometric designs and (bio)chemical/physical features are current key players in impacting technologies. Herein, we critically review the state of the art and future trends of biomaterial microparticles in contact with cells and tissues, excluding internalization studies, and with emphasis on innovative particle design and applications.